Awareness of SEC Enforcement and Auditor Reporting Decisions1. (3rd January 2018) - Defond, Mark L.; Francis, Jere R.; Hallman, Nicholas J.
Abstract: We find that non‐Big 4 audit offices with greater awareness of SEC enforcement are more likely to issue first‐time going‐concern reports to distressed clients; where SEC "awareness" is measured using (i) audit office proximity to SEC regional offices, and (ii) proximity to specific SEC enforcement actions against auditors. We also show that these non‐Big 4 audit offices issue more going‐concern opinions to clients who do not subsequently fail, indicating a conservative bias that reduces the informativeness of audit reports. This conservative reporting bias is also associated with higher audit fees and higher auditor switching rates. These findings are important because non‐Big 4 firms now audit 39 percent of SEC registrants and issue 88 percent of going‐concern audit reports. For Big 4 offices, we find some evidence that awareness of SEC enforcement may improve reporting accuracy by reducing Type II errors (failing to issue a going‐concern report to a company that fails), although the number of cases is small.